A Qualitative Approach towards the Understanding of Managerial Employees in Islamic Organizations - Abdullah, Azwan; Ismail, Mohammad; Yaacob, Mohd Rafi; Kamarudin, Mohd Khairy; Mohd Alwi, Mohd Afifie; Muhammad, Mohd Zulkifli; Wan Mohd Nasir, Wan Nadiah; Hilaluddin, Nusaibah (Jurnal Ilmiah Peuradeun, 2019)
The critique on the failure of Islamic organizations to represent the Islamic nature has been pointed towards employees’ competency in understanding the Islamic concept. Hence, this study seeks to delve into the understanding of the employee in Islamic organizations regarding the concept, implementation and challenges in such organizations by employing the qualitative method. The study involves three Islamic organizations namely Islamic Banking, Takaful and Islamic Property Management Company located in three states of the East Coast of Peninsular Malaysia i.e. Kelantan, Terengganu and Pahang. Managerial employees from the three organizations were interviewed and the outcomes were triangulated with the experts. The findings show understanding among managerial employees in Islamic organizations is appropriate but there are still more that need to be improved.